Proceedings for NPL Joint Symposium on Quantum Technologies 13th and 14th September 2022 (Journal of physics. Conference series, 2022)
The NPL Joint Symposium on Quantum Technologies was hosted as an in-person only meeting at NPL's facilities in Teddington, London on Tuesday 13th and Wednesday 14th September 2022.This symposium brought together an impressive collection of invited and contributing speakers from across the quantum industry and academia. The presentations provided a broad introduction and described the latest advances across all pillars of quantum technologies including:• Quantum Communication and Computation• Quantum Integrated Circuits and Interconnect• Quantum Imaging and Packaging• Quantum Metrology and StandardsThe authors of five contributed papers published in these proceedings were invited to present them alongside invited speakers.This conference was the 6th in a series of symposia organised jointly on behalf of the main international standards development organisations including IEC, ISO, ITU, CEN/CENELEC, IEEE, ETSI and BSI. BSI (the UK national standards body) and the IEEE UK and Ireland Photonics Chapter and Quantum Group provided strong support for these symposia.This was the first of the Joint Symposia to be held as an in-person event.List of titles Sponsorship and Collaborations, Chairs, Conference Organising Committee, Acknowledgements are available in this Pdf.